Preserving and expanding the role of on-motorized transport in Universiti Teknologi Malaysia (UTM) Skudai Campus - Oluwatosni, Oloruntobi Olakunle (2012)
Increase in the number of students and staffs often cause expansion of the university campus and make it obligatory to expand the role of transportation in the entire campus. However, increase in population also increases the automobile use and ownership among staffs and students and heavy traffic movement is gradually becoming incontrollable and shortages of parking spaces in the academic and administrative area is gradually increasing. The objective of this study is to investigate walking and cycling aspect of non-motorized transport in Universiti Teknologi Malaysia (UTM) Skudai campus including policy making and planning for the best ways to make university campus a better place for non-motorized transport usage. It will also investigates various planning and design concepts, and offers contributions to help to implement them and also look into problems confronting non-motorized transport in UTM Skudai campus and as well investigate the state of non-motorized transport facilities such as walkways, crosswalk, sidewalks, bike lanes etc. and recommend facilities improvements to ensure safety, access and providing features to accommodate people with disabilities too. Non-motorized transport traffic law enforcement, education and encouragement programs will be introduced and developed alongside with provision of modern facilities for non-motorized transport usage to improve walking and cycling conditions in the entire campus.